Successful treatment with daratumumab for post‐HSCT refractory hemolytic anemia. Issue 1 (22nd September 2019) - Even‐Or, Ehud; Naser Eddin, Adeeb; Shadur, Bella; Dinur Schejter, Yael; Najajreh, Mohammad; Zelig, Orly; Zaidman, Irina; Stepensky, Polina
Abstract: Autoimmune cytopenias (AIC) following allogeneic hematopoietic stem cell transplantation (HSCT) may cause significant morbidity and mortality and are often challenging to treat. We present a case of a pediatric patient with primary myelofibrosis of infancy caused by VPS45 protein deficiency, who developed severe refractory hemolytic anemia and immune‐mediated thrombocytopenia 3.5 months following HSCT. After the failure of several treatments, he received daratumumab, an anti‐CD38 specific antibody, and demonstrated fast and sustained response. The only side effect was delayed recovery of humoral immunity. Daratumumab, by targeting antibody‐producing plasma cells, may be a valid treatment option for refractory post‐HSCT AIC.